EDUCATION AS A BUILDING BLOCK IN OPENING UP GOVERNMENT DATA - Hyam Nashash (European Scientific Journal, ESJ, 2013)
This paper aimed at investigating the evolution of Open data concept and open government data initiatives as an ongoing dynamic process that needs continuous maintenance and collaborative updating process and has its own principles, challenges at each stage, as well as limitations and risks that will continue to emerge upon different and intergovernmental circumstances related to the social, political and economical context of each country and its system. Additionally, focus on the interrelated link with education as a fundamental aspect and a builging block for sustainable development that contributes strongly to economic growth. Where the OGD is the double facet as it serves educationists to develop their policies, plans and decisions accordingly and will empower public to understand and make use of the data and participate in decision and policy making.